2013
DOI: 10.3109/10903127.2013.831506
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Implementation and Operation of a Novel Paramedic Long-term Care Program

Abstract: The ECP program has positive implications for the relationship between EMS and LTC, requires additional paramedic training, and can positively affect LTC patient experiences during acute medical events. ECPs have a novel role to play in end-of-life care and find this new role rewarding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…These shifts occurred in terms of practice location (e.g., paramedics working in emergency department or clinics) [30] but also models of care [1, 11, 31]. For instance, paramedicine was no longer viewed as exclusively emergency response based, offering more in terms of contributions to health and health care:…”
Section: Resultsmentioning
confidence: 99%
“…These shifts occurred in terms of practice location (e.g., paramedics working in emergency department or clinics) [30] but also models of care [1, 11, 31]. For instance, paramedicine was no longer viewed as exclusively emergency response based, offering more in terms of contributions to health and health care:…”
Section: Resultsmentioning
confidence: 99%
“…35 Some studies have explored the complexity of transport decisions and the many factors that must be considered by EMS responders. 36,37 Many of the 33 studies included in this review include strategies within the programs reported to provide patients with access to other services, expanded care on scene, or other means of transport to the ED. The body of knowledge related to "mobile integrated healthcare" or "community paramedicine" has become multi-faceted and complex, with many services tailored specifically for the population or community they are aiming to better serve.…”
Section: Alternatives To Transportmentioning
confidence: 99%
“…176 Two studies on decision-making by ambulance staff for patients with epilepsy 174 and elderly fallers 175 both identified a need for additional training and support to aid safe decision-making, as did one Canadian study that focused on out-of-hospital management of patients with long-term conditions. 182 …”
Section: Safety and Decision-makingmentioning
confidence: 99%